2010
DOI: 10.1080/19393210.2010.503329
|View full text |Cite
|
Sign up to set email alerts
|

Survey of pesticide residues in maize, cowpea and millet from northern Cameroon: part I

Abstract: In northern Cameroon, the misuse of pesticides for pest control is common among small-scale farmers. Therefore, monitoring of pesticide residues was carried out on stored maize, cowpea and millet from eight localities. The determination of residues of organochlorines (lindane, α-endosulfan and β-endosulfan), organophosphorus compounds (malathion and pirimiphos-methyl), synthetic pyrethroids (permethrin) and carbamates (carbufuran) was performed using GC-ECD/NPD and GC-MS for confirmation. Organochlorine pestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 9 publications
4
21
1
Order By: Relevance
“…In maize, cowpea, and millet samples from northern Cameroon, organochlorine and organophosphorus pesticides including β-endosulfan, lindane, pirimiphos-methyl, and malathion were detected more frequently [10]. Moreover, Sonchieu et al [5] found that in cowpea samples from the markets of Ngaoundéré in northern Cameroon, residues of the organophosphorus pesticides dichlorvos, methyl-parathion, malathion, profenofos, diazinon, and chlorpyrifos were found in concentrations ranging from 0.02 to 5.4 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In maize, cowpea, and millet samples from northern Cameroon, organochlorine and organophosphorus pesticides including β-endosulfan, lindane, pirimiphos-methyl, and malathion were detected more frequently [10]. Moreover, Sonchieu et al [5] found that in cowpea samples from the markets of Ngaoundéré in northern Cameroon, residues of the organophosphorus pesticides dichlorvos, methyl-parathion, malathion, profenofos, diazinon, and chlorpyrifos were found in concentrations ranging from 0.02 to 5.4 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are comparable to the findings of Bempah and Donkor [29], who reported 32.8% of fruit samples with residues above MRLs, and Mekonen et al [2], in which one-third of samples were above the MRLs. However, Sonchieu et al [10] obtained higher values, with 75% of samples containing pesticide residues above MRLs. These disparities could be due to the single food item (cowpea) used in their study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of OPPs as post harvest pesticides is mainly due to the lower rate of degradation under the storage conditions that exist in storehouses.The post-harvest pesticides have been attracting much attention because their residues in stored cereal grains may be hazardous to human health [8]. The presence of OPPs residues in corn is still reported [9,10]. The monitoring of pesticide residues in corn and corn products is of a significant importance in terms of consumer safety.…”
Section: Introductionmentioning
confidence: 99%